ANALISIS LITERASI DAN INKLUSI PERBANKAN SYARIAH PADA MAHASISWA/I STRATA-1 FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS RIAU - Kaswina Irya Rabiatul; Rosyetti Rosyetti; Widayatsari Any (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research aims to know at Islamic banking literacy in Strata-1 students of the Faculty of Economics and Business, University of Riau, to know the inclusion of Islamic banking in Strata students of the Faculty of Economics and Business, University of Riau, and to know the relationship between banking literacy and inclusion syariah for Strata-1 students of the Faculty of Economics and Business, University of Riau. This research used Slovin techniques and simple random sampling, so 100 samples were selected. The analytical method used in this research is quantitativee descriptive method and Pearson correlation analysis with the help of SPSS statistical tools. 24. The results of this study indicate that Islamic banking literacy in Strata-1students of the Faculty of Economics and Business, University of Riau is in the sufficient literate category, namely 74,61%, the inclusion of Islamic banking in Strata-1 students of the Faculty of Economics and Business, University of Riau is at medium category by 54%, and based on the test based on what has been done it can be seen that there is a significant positive relationship between Islamic banking literacy and Islamic banking inclusion.Keywords: Islamic banking literacy, Islamic banking inclusion.